Cost of dengue and other febrile illnesses to households in rural Cambodia: a prospective community-based case-control study - Margolis Harold S; Duong Socheat; Ngan Chantha; Beatty Mark; Wichmann Ole; Huy Rekol; Vong Sirenda (BMC, 2009)
Abstract Background The average annual reported dengue incidence in Cambodia is 3.3/1,000 among children < 15 years of age (2002-2007). To estimate the economic burden of dengue, accurate cost-of-illness data are essential. We conducted a prospective, community-based, matched case-control study to assess the cost and impact of an episode of dengue fever and other febrile illness on households in rural Cambodia. Methods In 2006, active fever surveillance was conducted among a cohort of 6,694 children aged ≤ 15 years in 16 villages in Kampong Cham province, Cambodia. Subsequently, a case-control study was performed by individually assigning one non-dengue febrile control from the cohort to each laboratory-confirmed dengue case. Parents of cases and controls were interviewed using a standardized questionnaire to determine household-level, illness-related expenditures for medical and non-medical costs, and estimated income loss (see Additional file <supplr sid="S1">1</supplr>). The household socio-economic status was determined and its possible association with health seeking behaviour and the ability to pay for the costs of a febrile illness. <suppl id="S1"> Additional File 1 <text> 2006 cost study survey questionnaire, Cambodia. the questionnaire represents the data collection instrument that was developed and used during the present study. </text> <file name="1471-2458-9-155-S1.pdf"> Click here for file </file> </suppl> Results Between September and November 2006, a total of 60 household heads were interviewed: 30 with dengue-positive and 30 with dengue-negative febrile children. Mean total dengue-related costs did not differ from those of other febrile illnesses (31.5 vs. 27.2 US$, p = 0.44). Hospitalization almost tripled the costs of dengue (from 14.3 to 40.1 US$) and doubled the costs of other febrile illnesses (from 17.0 to 36.2 US$). To finance the cost of a febrile illness, 67% of households incurred an average debt of 23.5 US$ and higher debt was associated with hospitalization compared to outpatient treatment (US$ 23.1 vs. US$ 4.5, p < 0.001). These costs compared to an average one-week expenditure on food of US$ 9.5 per household (range 2.5-21.3). In multivariate analysis, higher socio-economic status (odds ratio [OR] 4.4; 95% confidence interval [CI] 1.4-13.2), duration of fever (OR 2.1; 95%CI 1.3-3.5), and age (OR 0.8; 95%CI 0.7-0.9) were independently associated with hospitalization. Conclusion In Cambodia, dengue and other febrile illnesses pose a financial burden to households. A possible reason for a lower rate of hospitalization among children from poor households could be the burden of higher illness-related costs and debts.